A randomised trial comparing endometrial resection and abdominal hysterectomy for the treatment of menorrhagia. Issue 6814 (30th November 1991) - Gannon, M J; Holt, E M; Fairbank, J; Fitzgerald, M; Milne, M A; Crystal, A M; Greenhalf, J O
Abstract : OBJECTIVE–To determine the advantages and disadvantages of endometrial resection and abdominal hysterectomy for the surgical treatment of women with menorrhagia. DESIGN–Randomised study of two treatment groups with a minimum follow up of nine months. SETTING–Royal Berkshire Hospital, Reading. SUBJECTS–51 of 78 menorrhagic women without pelvic pathology who were on the waiting list for abdominal hysterectomy. TREATMENT–Endometrial resection or abdominal hysterectomy (according to randomisation). Endometrial resections were performed by an experienced hysteroscopic surgeon; hysterectomies were performed by two other gynaecological surgeons. MAIN OUTCOME MEASURES–Length of operating time, hospitalisation, recovery; cost of surgery; short term results of endometrial resection. RESULTS–Operating time was shorter for endometrial resection (median 30 (range 20-47) minutes) than for hysterectomy (50 (39-74) minutes). The hospital stay for endometrial resection (median 1 (range 1-3) days) was less than for hysterectomy (7 (5-12) days). Recovery after endometrial resection (median 16 (range 5-62) days) was shorter than after hysterectomy (58 (11-125) days). The cost was 407 pounds for endometrial resection and 1270 pounds for abdominal hysterectomy. Four women (16%) who did not have an acceptable improvement in symptoms after endometrial resection had repeat resections. No woman has required hysterectomy during a mean follow up of one year. CONCLUSION–For women with menorrhagia who have no pelvic pathology endometrial resection is a useful alternative to abdominal hysterectomy, with many short term benefits. Larger numbers and a longer follow up are needed to estimate the incidence of complications and the long term efficacy of endometrial resection.